2010
DOI: 10.1073/pnas.1011975107
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids in the prefrontal cortex enhance memory consolidation and impair working memory by a common neural mechanism

Abstract: It is well established that acute administration of adrenocortical hormones enhances the consolidation of memories of emotional experiences and, concurrently, impairs working memory. These different glucocorticoid effects on these two memory functions have generally been considered to be independently regulated processes. Here we report that a glucocorticoid receptor agonist administered into the medial prefrontal cortex (mPFC) of male Sprague-Dawley rats both enhances memory consolidation and impairs working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
169
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(188 citation statements)
references
References 49 publications
(76 reference statements)
10
169
2
2
Order By: Relevance
“…These results suggest that the infralimbic cortex could contribute to the formation of aversive memory, in part, by increasing corticosterone concentrations. The involvement of corticosterone increases, immediately after training, enhancing the formation of aversive memory has been previously reported [36,37].…”
Section: Discussionmentioning
confidence: 53%
“…These results suggest that the infralimbic cortex could contribute to the formation of aversive memory, in part, by increasing corticosterone concentrations. The involvement of corticosterone increases, immediately after training, enhancing the formation of aversive memory has been previously reported [36,37].…”
Section: Discussionmentioning
confidence: 53%
“…PFC function is enhanced under low to moderate acute stress (Yuen et al, 2009). Under high stress, norepinephrine levels and dopamine levels rise and shut down the PFC (Arnsten, 2000;Barsegyan, Mackenzie, Kurose, McGaugh, & Roozendaal, 2010;Birnbaum, Podell, & Arnsten, 2000;Roozendaal, McReynolds, McGaugh, 2004). There appears to be a narrow range for optimal norepinephrine (Aston-Jones & Cohen, 2005) and dopamine activity in the PFC (Arnsten & Goldman-Rakic, 1998;Murphy, Arnsten, Goldman-Rakic, & Roth, 1996;Zahrt, Taylor, Mathew, &Arnsten, 1997).…”
Section: Effects Of Stress On Memory-related Brain Regionsmentioning
confidence: 99%
“…Memory consolidation via the hippocampus is left relatively intact, to encode stressful events as a survival mechanism (Barsegyan, Mackenzie, Kurose, McGaugh, & Roozendaal, 2010;Liang, 2001;Roozendaal, McReynolds, McGaugh, 2004). As a consequence of this ability to better remember aversive events, our ability to retrieve and modulate information under stress may suffer.…”
Section: Effects Of Stress On Memory-related Brain Regionsmentioning
confidence: 99%
“…Animal studies showed that corticosterone and norepinephrine (NE) act together to facilitate memory formation through actions involving the amygdala, hippocampus, and prefrontal cortex (PFC) [10,12]. More recently, glucocorticoids and the noradrenergic system were shown to interact in the medial PFC in producing working memory impairment [13]. In addition, the capability of these systems to influence learning processes depending on other brain systems -such as the dorsal striatum -was also shown [14].…”
Section: Stress Mediators: Glucocorticoids and Norepinephrinementioning
confidence: 99%